Common Fixed Point Theorems in a New Fuzzy Metric Space - Weiquan Zhang; Dong Qiu; Zhifeng Li; Gangqiang Xiong (Journal of Applied Mathematics, 2012)
We generalize the Hausdorff fuzzy metric in the sense of Rodríguez-López and Romaguera, and we introduce a new M∞-fuzzy metric, where M∞-fuzzy metric can be thought of as the degree of nearness between two fuzzy sets with respect to any positive real number. Moreover, under ϕ-contraction condition, in the fuzzy metric space, we give some common fixed point theorems for fuzzy mappings.